Kajian Studi Literatur : Pelatihan Untuk Pengembangan Karyawan UMKM - Saifur Rijal, Muhammad; Sopiah, Sopiah (Jurnal Ilmu Manajemen Terapan, 2023)
The purpose of this research is to conduct a systematic review of literature related to employee development in SMEs and to provide a deeper understanding of employee development in SMEs and identify best practices that can help employee development in SMEs. The method used in this research is a systematic literature review. Data were taken from online databases such as Google Scholar, ScienceDirect, and ProQuest. The keywords used in the search were "employee development" and "SMEs." Subsequently, the researchers selected articles that met the inclusion and exclusion criteria. The novelty of this research is the application of SLR on the topic of employee development in SMEs, which has not been extensively researched before. In addition, this research can provide insights into best practices in employee development in SMEs. The results of this research indicate that employee development in SMEs can improve employee performance and company productivity. Best practices in employee development in SMEs include continuous training and development of employees, recognition of employee contributions, and career development programs.